Labor Migration Policy in ASEAN States - Romadhona, Mochamad Kevin; Kinasih, Sri Endah; Oktafenanda, Rachmat Dimas (International Law Discourse in Southeast Asia, 2025)
Labor migration has become a major trend in Southeast Asia, with Indonesia being one of the largest sending countries. Indonesian migrant workers (PMI) significantly contribute to the economy through remittances, but also face numerous challenges, including human rights violations and undocumented employment. This study examines Indonesia's responsibility to protect its migrant workers, in line with national legislation and international human rights standards. This is qualitative research that uses secondary data to examine social issues and individual activities, focusing on Indonesian migrant workers' protection, using a case study approach for in-depth examination. Indonesia has implemented various regulations to protect migrant workers, including the Indonesian Migrant Worker Protection Law ratified in 2017. The new legislation transfers responsibility for IMW protection to the central government, ensuring human rights and safeguards for IMW and their families. The Protection of Indonesian Workers (IMW) is a national policy designed to safeguard IMW's rights and uphold human rights. The government also establishes a task force to address legal matters concerning migrant workers overseas.